Magnetic characterization of a retroarc extensional basin: The Loncopué Trough - Pesce, Agustina (2019)
The Loncopué Trough is a Pliocene to Quaternary extensional basin developed over the hinterland area of the Southern Central Andes. This basin is bounded by two neotectonic extensional fault systems delimiting a narrow topographic low. Previous studies have mostly focused on structural and geochemical aspects of this feature. However, geophysical surveys, aimed to unravel deep structure beneath a thick-younger than 5 My volcanic coverage, are scarce and based their interpretations on low resolution data sets. In this study, we collected new aeromagnetic data with the objective of characterizing the magnetic properties of the crust in the Loncopué Through and nearby zones. Additionally, we analyze the spatial relation between geological structures, volcanic fields and magnetic data. In order to highlight the boundaries of the magnetic sources and calculate the basement depth, we applied derivative techniques and the source parameter imaging. Also, we estimated an effective susceptibility model using the Magnetization Vector Inversion method, which takes into account the combined effects of remanence and induced magnetization. To determine the thermal structure of the area, we calculated the Curie depth points through the spectral analysis technique. From the analysis of magnetic data we were able to characterize the main structures and lineaments associated with this retroarc extensional trough. Notably, only the Loncopué eastern fault system seems to be a crustal-scale tectonic feature, while E-W-, ENE- and ESE-trending lineaments are interpreted as relatively minor structures segmenting the basement. Finally, our susceptibility model, together with the analysis of the Curie point, revealed potential magmatic/hydrothermal reservoirs in the Copahue volcano, and the Codihue and Cajón de Almanza regions that could be connected at depth forming a regional magmatic body.